2012
DOI: 10.1074/jbc.m111.302299
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Chemokine (CXC Motif) Ligand 12/Chemokine (CXC Motif) Receptor 4 Axis (CXCL12/CXCR4)-mediated Cell Migration by Targeting Mammalian Target of Rapamycin (mTOR) Pathway in Human Gastric Carcinoma Cells

Abstract: CXCL12/CXCR4 plays an important role in metastasis of gastric carcinoma. Rapamycin has been reported to inhibit migration of gastric cancer cells. However, the role of mTOR pathway in CXCL12/CXCR4-mediated cell migration and the potential of drugs targeting PI3K/mTOR pathway remains unelucidated. We found that CXCL12 activated PI3K/Akt/mTOR pathway in MKN-45 cells. Stimulating CHO-K1 cells expressing pEGFP-C1-Grp1-PH fusion protein with CXCL12 resulted in generation of phosphatidylinositol (3,4,5)-triphosphate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(53 citation statements)
references
References 29 publications
5
48
0
Order By: Relevance
“…In addition, pretreatment with pertussis toxin, a G i protein inhibitor, abolished the activation of Akt at S473 induced by CXCL12. This is in line with reports in T lymphocytes and gastric cancer cells showing that G i protein is required for CXCL12-induced activation of PI3K and Akt at S473 [12,38]. Taken together these findings provide mechanistic insight into how CXCL12/CXCR4 signals to mTORC2 in EC (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In addition, pretreatment with pertussis toxin, a G i protein inhibitor, abolished the activation of Akt at S473 induced by CXCL12. This is in line with reports in T lymphocytes and gastric cancer cells showing that G i protein is required for CXCL12-induced activation of PI3K and Akt at S473 [12,38]. Taken together these findings provide mechanistic insight into how CXCL12/CXCR4 signals to mTORC2 in EC (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…To date there has been a paucity of information on the molecular mechanism of CXCL12/CXCR4 signal transduction in EC as most studies have focused on signal transduction in tumor cells [12,13,6]. mTORC2 is emerging as a central player in the promotion of cell migration via chemotactic receptors [2729,16], however, the molecular connections linking receptors to mTORC2 activation is poorly understood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Dubrovska et al[30] demonstrated the direct regulation of CXCR4 expression by the PI3K pathway and thus implied a mutually positive regulatory feedback loop between the PI3K/AKT and CXCR4/CXCL12 signaling pathways, which are both important for cancer metastasis. Furthermore, our previous results indicated that HBV-X protein induced the expression of AFP in human normal liver cells, which correlated to CXCR4 expression in human hepatoma cells[31], and accumulated evidences showed that the mTOR/CXCR4 signal axis is closely associated with the promotion of cancer cell metastasis[32]. In the present study, we also explored the possible mechanisms by which AFP can regulate CXCR4 expression via knockdown of AFP in PLC/PRF/5 cells or appearance of AFP in pcDNA3.1- afp vectors transfected HLE cells.…”
Section: Discussionmentioning
confidence: 99%